India-Bangladesh Relations in 2024: Navigating Change and Continuity - Maiti, Malayendu (International Journal of Advanced Research in Peace, Harmony and Education; Vol 10 No 1 (2025): International Journal of Advance Research in Peace, Harmony and Education, 2025)
India and Bangladesh share a multifaceted relationship shaped by historical ties, economic interdependence, and strategic cooperation. In 2024, the bilateral dynamic continues to evolve, balancing elements of continuity and change. Political interactions remain crucial, especially in the context of Bangladesh’s domestic political landscape and India’s strategic interests in the region. Economic engagement, including trade agreements, connectivity projects, and energy cooperation, remains a cornerstone of the relationship. Security concerns, particularly border management, counterterrorism efforts, and the Rohingya crisis, continue to demand collaborative solutions. Water-sharing issues, including the pending Teesta River agreement, and environmental challenges, such as climate change and the Sundarbans’ conservation, also influence bilateral ties. Moreover, the growing presence of China in Bangladesh’s economic and infrastructure sectors presents a strategic challenge for India. The two nations also cooperate in regional forums like BIMSTEC and SAARC, reflecting their broader geopolitical considerations. Despite occasional challenges, India and Bangladesh continue to seek a stable and mutually beneficial partnership. This article examines the key developments in 2024, assessing political, economic, security, and environmental aspects while exploring future prospects for cooperation.